Influence of Cover Crops on Management of Amaranthus Species in Glyphosate- and Glufosinate-Resistant Soybean. (15th August 2017) - Loux, Mark M.; Dobbels, Anthony F.; Bradley, Kevin W.; Johnson, William G.; Young, Bryan G.; Spaunhorst, Douglas J.; Norsworthy, Jason K.; Palhano, Matheus; Steckel, Lawrence E.
Abstract : A field study was conducted for the 2014 and 2015 growing season in Arkansas, Indiana, Illinois, Missouri, Ohio, and Tennessee to determine the effect of cereal rye and either oats, radish, or annual ryegrass on the control of Amaranthus spp. when integrated with comprehensive herbicide programs in glyphosate-resistant and glufosinate-resistant soybean. Amaranthus species included redroot pigweed, waterhemp, and Palmer amaranth. The two herbicide programs included were: a PRE residual herbicide followed by POST application of foliar and residual herbicide (PRE/POST); or PRE residual herbicide followed by POST application of foliar and residual herbicide, followed by another POST application of residual herbicide (PRE/POST/POST). Control was not affected by type of soybean resistance trait. At the end of the season, herbicides controlled 100 and 96% of the redroot pigweed and Palmer amaranth, respectively, versus 49 and 29% in the absence of herbicides, averaged over sites and other factors. The PRE/POST and PRE/POST/POST herbicide treatments controlled 83 and 90% of waterhemp at the end of the season, respectively, versus 14% without herbicide. Cover crop treatments affected control of waterhemp and Palmer amaranth and soybean yield, only in the absence of herbicides. The rye cover crop consistently reduced Amaranthus spp. density in the absence of herbicides compared to no cover treatment.